Textural and functional properties of surimi from striped catfish Pangasianodon hypophthalmus (Sauvage, 1878) as affected by natural spice extracts - Majumdar, Ranendra K.; Saha, Apurba; Maurya, Pradip K.; Roy, Deepayan; Shitole, Snehal; Balange, Amjad K. (Indian Journal of Fisheries, 2016)
Effects of aqueous extract of natural spices such as garlic, clove and cinnamon on the textural and functional properties ofÂ surimi gel from Striped catfish, Pangasianodon hypophthalmus (Sauvage, 1878) was studied and a positive effect was observed.Â Different levels of extract (0.5, 1.0, 1.5 and 2.0%, w/w) were used. Protein solubility significantly (p